Projeto nazista de desumanização: análise das relações sociopolíticas no campo de concentração na obra É isto um homem? de Primo Levi (1947) - Calheiros, Letícia Martins (2023)
This research aims to carry out an analysis of sociopolitical relations in the concentration camp from the testimony of experience of the Italian Jew Primo Levi (1919-1987) in the work Is this a man? of 1947. The accounts produced by the author during his time in the Auschwitz-Monowitz labor camp, between 1944 and 1945, will be used as a source to identify the possible sociopolitical relations reported by Levi in his confinement. From what the author brings as a Nazi plan of dehumanization of its prisoners, it is intended to relate the execution of the purpose of the Germans with interpersonal bonds found in his book, to produce an analysis about how the daily relations between the prisoners contributed or not to the process of dehumanization. In this way, Primo Levi in Is this a man? realizes in its course a reflection on the human condition within that new reality, which is the concentration camp - in his case, Auschwitz. Within this consideration, the author questions what they, as prisoners, lost, or rather, was taken from them: their possessions, their families, their homes, their dreams, their rights, their lives, their identities and even their names. In view of this, this work proposes to answer the following questions: 1) what is the Nazi objective with the dehumanization plan? 2) What are the types of socio-political relations reported by Primo Levi in his work? 3) how did the socio-political relations in the concentration camp narrated in Primo Levi's work, Is this a man? hindered or contributed to the dehumanization of those persecuted by the Nazi regime? To answer these questions, the main analysis bias chosen was that of Emotions, both through the History of Emotions and through the Anthropology and Sociology of Emotions. These allowed us to analyze the sociopolitical relations reported by Levi and to understand the way in which they were important for the partial failure of the Nazi regime's dehumanization plan.